The Impact Of The First Phase Of The Ikn Development Program On The Financial Performance Of Construction Service Companies Listed On The IDX - Hutajulu, Novita Sari; Alfiana Antoh; Ulfah R Muslimin (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This study aims to analyze the differences in financial performance before and during the first phase of the IKN development, measured by Return On Asset, Current Ratio, and Debt to Equity Ratio. The research utilizes a sample of construction service companies listed on the Indonesia Stock Exchange (BEI) during the period of 2018-2023. The analysis employs Paired Sample T-Test and Wilcoxon Signed Rank Test using SPSS 29. The findings of this research are as follows: (1) there is a significant difference in Return On Asset before and during the first phase of the IKN development program; (2) there is no significant difference in Current Ratio before and during the first phase of the IKN development program; (3) there is no significant difference in Debt to Equity Ratio before and during the first phase of the IKN development program.